ความสาคัญของพระพุทธศาสนาต่อสังคมไทย - ใครบุตร, ทวีศักดิ์ (วารสารศรีล้านช้างปริทรรศน์, 2017)
สังคมไทยเป็นสังคมที่มีพระพุทธศาสนาเป็นเอกลักษณ์  เป็นสังคมของชาวพุทธ กล่าวคือ ประชาชนชาวไทยนับตั้งแต่องค์พระมหากษัตริย์ลงมา ได้อาศัยหลักคำสอนในพระพุทธศาสนายึดถือเป็นหลักปฏิบัติในการดำเนินชีวิตตลอดมา ซึ่งทำให้อุปนิสัยใจคอของคนไทยมีลักษณะพิเศษที่แตกต่างจากชนชาติอื่นอย่างเห็นได้ชัด เช่น การยิ้มแย้มแจ่มใส ความเป็นมิตรกับทุกคนและต้อนรับแขกแปลกหน้าที่มาเยี่ยมเยียนด้วยน้ำใจไมตรีอันอบอุ่น ปัญหาความขัดแย้งระหว่างคนไทยกับคนต่างชาตินับว่ามีน้อยมาก ทั้งนี้เพราะคนไทยได้รับนับถือพระพุทธศาสนาอย่างมั่นคง ประชากรประมาณร้อยละ ๙๕ นับถือพระพุทธศาสนา พระพุทธศาสนาในสังคมไทยโดยส่วนใหญ่มักจะผสมกับลัทธิวิญญาณ พฤติกรรมทางศาสนาที่แสดงออกจึงมีทั้งการไหว้พระและนับถือผี การดำเนินชีวิตของคนไทยมีลักษณะเรียบง่าย อ่อนน้อมถ่อมตน คนไทยจึงอบอุ่นมีจิตใจอ่อนโยน ชอบความยุติธรรมโดยเฉพาะอย่างยิ่งไม่นิยมความรุนแรงในการแก้ปัญหา เอกลักษณ์ทางค่านิยมและนิสัยใจคอ เช่น การมีน้ำใจเอื้อเฟื้อเผื่อแผ่ การรักความเป็นอิสระ การรักความสนุกสนานรื่นเริง การมีสัมมาคารวะต่อผู้อาวุโส  คำสอนของพระพุทธศาสนาในฐานะที่เป็นเครื่องกำกับพฤติกรรมที่แสดงออกทางกาย วาจาและจิตใจของคนไทย ถือได้ว่า หลักธรรมคำสอนในพระพุทธศาสนาเป็นมรดกแห่งอารยธรรมทางปัญญาของมนุษยชาติ ทื่อำนวยประโยชน์สุขเป็นอันมากให้กับชาวโลกโดยเฉพาะอย่างยิ่งภูมิปัญญาอันสูงส่งที่สามารถทำให้มนุษย์ ได้พบสันติภาพ อิสรภาพ และความรักอันยิ่งใหญ่ เป็นที่ยอมรับขององค์การสหประชาชาติ  เพราะพระพุทธศาสนาอุบัติขึ้นมาโดยมีมนุษยชาติเป็นศูนย์กลางนั่นเอง   Thai society, the society of the Buddhist, was obviously characterized by Buddhism. As said, most of Thai people, from the king to common persons, believed in and behaved themselves under the Buddhist principles as their living ways. So, Thai character, which was regarded as smile, friendliness and a warm welcome to strangers, seemed distinctly different from other nations. The problem on conflicts or disagreement between Thais and foreigners was likely found because most of Thai people, about 95%, believed in Buddhism. However, Buddhism in Thai society was mostly mixed with local people’s animism. The religious behavior of those people was complicated together with paying respect to Buddhist monks and worshipping the spirits or ghosts. As regards, Thai living life looked very simple, submissive, and modest, and Thai people seemed friendly,  good-natured, well-mannered, and justice-loving. Especially, Thai people solved any problem without violence. Such traits of Thai people’s values and characters as generosity, freedom-loving, pleasure-loving, and reverence to the senior, were derived from Buddhism as a tool to control Thai people’s physical, verbal and mental behaviors. As regards, the teachings in Buddhism were counted as a heritage of wisdom civilization for mankind, giving the worldwide people blisses. Proclaimed by the United Nations, the sublime wisdom of Buddhism was specially accepted to lead the people to meet peace, independence and enormous love because Buddhism was the humankind-centered religion.